2020
DOI: 10.7150/ijms.49053
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of TPX2-related ceRNA network as prognostic biomarkers in lung adenocarcinoma

Abstract: Background and aim: Competing endogenous RNA (ceRNA) is believed to play vital roles in tumorigenesis. The goal of this study was to screen prognostic biomarkers in lung adenocarcinoma (LUAD). Methods: Common differentially expressed genes (DEGs) were collected from Gene Expression Omnibus (GEO) databases and The Cancer Genome Atlas databases (TCGA) using GEO2R and "limma" package in R, respectively. Overlapping DEGs were conducted using enrichment of functions and protein-protein interaction (PPI) network to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Long noncoding RNAs (lncRNAs) longer than 200 bp can interact with mRNAs, miRNAs, and circulating RNAs to participate in a complex network of gene expression regulation. 4 Insights into the function of a few characteristic lncRNAs suggested a surprising diversity of cellular processes, from chromatin modification, transcription, splicing, and translation to cell differentiation, cell cycle regulation, and stem cell reprogramming. 5 lncRNAs are involved in the development of some cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) longer than 200 bp can interact with mRNAs, miRNAs, and circulating RNAs to participate in a complex network of gene expression regulation. 4 Insights into the function of a few characteristic lncRNAs suggested a surprising diversity of cellular processes, from chromatin modification, transcription, splicing, and translation to cell differentiation, cell cycle regulation, and stem cell reprogramming. 5 lncRNAs are involved in the development of some cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, numerous studies have analyzed the association between TPX2 and human malignancy (12)(13)(14). To the best of our knowledge, the present study is the first to focus on TPX2 function in osteosarcoma.…”
Section: Discussionmentioning
confidence: 88%
“…A number of studies have reported that the activation of TPX2 is associated with a variety of different cancer types (12)(13)(14)(15), but the molecular mechanisms underlying TPX2 function in osteosarcoma are not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the ceRNA network has been widely studied and it has been shown that ceRNA affects the development of numerous cancers, for example, lung cancer, 93 , 94 breast cancer, 95 and gastric cancer. 32 It was also studied in COPD, 35 but it was deficient.…”
Section: Discussionmentioning
confidence: 99%